1954
DOI: 10.1121/1.1907401
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Polarization Effects in Barium Titanate Ceramics

Abstract: The electromechanical coupling in barium titanate ceramics is studied as a function of external bias for thickness resonances in the ultrasonic frequency range. The losses associated with the heating of resonant transducers are shown to be primarily of mechanical rather than dielectric origin. The response near coercive field strengths indicates that the rearrangements of domain patterns take place in at least two separate forms. The relationships of the subsidiary responses, which are observed in ceramics und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For continuous operation, in which the heating due to losses associated with a hysteresis loop can cause the temperature to exceed the Curie point, they showed that biasing could reduce the hysteresis loop area, achieving temperature stabilization, and allowing higher drive fields. Hueter et al 7 followed up on the loss-factor reduction aspects of Ref. 6, but a͒ Currently on Intergovernmental Personnel Act ͑IPA͒ assignment at NUWC, Newport, RI 02841. noted that when mechanical losses are dominant ͑in comparison with dielectric losses͒, biasing does not provide much benefit.…”
Section: Introductionmentioning
confidence: 99%
“…For continuous operation, in which the heating due to losses associated with a hysteresis loop can cause the temperature to exceed the Curie point, they showed that biasing could reduce the hysteresis loop area, achieving temperature stabilization, and allowing higher drive fields. Hueter et al 7 followed up on the loss-factor reduction aspects of Ref. 6, but a͒ Currently on Intergovernmental Personnel Act ͑IPA͒ assignment at NUWC, Newport, RI 02841. noted that when mechanical losses are dominant ͑in comparison with dielectric losses͒, biasing does not provide much benefit.…”
Section: Introductionmentioning
confidence: 99%